2011
DOI: 10.1111/j.1472-765x.2011.03143.x
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of micro-organisms in processed soy products with an automated most probable number method compared with standard plate method

Abstract: Aim:  The automated TEMPO system (bioMerieux) is based on the most probable number (MPN) method for the enumeration of micro‐organisms in foods. In this study, we evaluated the performance of the TEMPO system as a diagnostic tool in comparison with the standard method in processed soy products. Methods and Results:  A verification study was conducted using artificially contaminated soy product samples such as soy protein isolate, water‐soluble soy polysaccharides, soy milk and processed soy food. Five types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The TEMPO system is an automated most probable number (MPN), which is based on the measurements of fluorescence method for enumerating aerobic bacteria and specific pathogens in foods [48][49][50]. Further, our results are in accordance with those observed by Katase and Tsumura [51], Blagoeva et al [52], and Łobacz et al [53], who compared the results of the TEMPO system with the corresponding methods to enumerate total aerobic bacteria, coliforms, Enterobacteriaceae, yeast and mold, S. aureus, and lactic acid bacteria. Moreover, comparisons of different methods for quantifying L. monocytogenes biofilms have shown that among the indirect counting methodologies, the one that gives the best results is the TEMPO system [54].…”
Section: Bacterial Enumeration On Polymer Surfacessupporting
confidence: 90%
“…The TEMPO system is an automated most probable number (MPN), which is based on the measurements of fluorescence method for enumerating aerobic bacteria and specific pathogens in foods [48][49][50]. Further, our results are in accordance with those observed by Katase and Tsumura [51], Blagoeva et al [52], and Łobacz et al [53], who compared the results of the TEMPO system with the corresponding methods to enumerate total aerobic bacteria, coliforms, Enterobacteriaceae, yeast and mold, S. aureus, and lactic acid bacteria. Moreover, comparisons of different methods for quantifying L. monocytogenes biofilms have shown that among the indirect counting methodologies, the one that gives the best results is the TEMPO system [54].…”
Section: Bacterial Enumeration On Polymer Surfacessupporting
confidence: 90%
“…These values can be ranked as good in method comparison studies according to correlation ranking index described by Ferrati et al (2005). Similarly in the study of Katase and Tsumura (2011), a remarkable correlation (r = 0.96) was determined between TEMPO STA and mannitol salt agar in artificially contaminated processed soy products.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, rapid identification of bacteria is as important as enumeration of bacteria (Katase and Tsumura, 2011;Tsumura and Tsuboi, 2012;Katase et al, 2013).…”
Section: Introductionmentioning
confidence: 99%